Shakespeare's Metrical Art - Wright, George T. (George Thaddeus) (Book collections on Project MUSE., 1991)
This is a wide-ranging, poetic analysis of the great English poetic line, iambic pentameter, as used by Chaucer, Sidney, Milton, and particularly by Shakespeare. George T. Wright offers a detailed survey of Shakespeare's brilliantly varied metrical keyboard and shows how it augments the expressiveness of his characters' stage language.